Global Climate Risk Index 2021: Who Suffers Most from Extreme Weather Events? - Eckstein, David; Kunzel, Vera; Shafer, Laura (German Watch, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:R6827BCW 2405685:GJDSJQFE

Ed-tech within limits: Anticipating educational technology in times of environmental crisis - Selwyn, Neil (E-Learning and Digital Media, 2021)
Despite climate heating and rising ecological instability, environmental issues feature rarely in discussions of educational technology. Most commentators presume the continued unfettered use of digital education resources bolstered by occasional claims that emerging technologies might support the ‘greening’ of school and university provision. In contrast to such business-as-usual complacency, this article anticipates ongoing environmental degradation of the planet as radically upending the continued expansion of digital technologies in education. On the one hand, depletion of natural resources and energy curtailments might put paid to established ‘abundant’ forms of digital technology use. On the other hand, more frequent climate-related disasters might necessitate emergency forms of education for displaced and unsettled populations. As such, the article argues for a new paradigm of educational technology that is both wholly sustainable and targeted towards displaced and disadvantaged populations. The article considers a number of ways that such an ‘Ed-Tech Within Limits’ might be pursued – outlining fundamental shifts in thinking necessary to reorient educational technology along environmentally concerned lines.
Publisher: SAGE Publications KerkoCite.ItemAlsoKnownAs: 10.1177/20427530211022951 2339240:U4D6A632 2405685:7JJ9CIWZ

Ed-Tech Within Limits: Anticipating educational technology in times of environmental crisis - Selwyn, Neil (E-Learning and Digital Media, 2021)
Despite climate heating and rising ecological instability, environmental issues feature rarely in discussions of educational technology. Most commentators presume the continued unfettered use of digital education resources bolstered by occasional claims that emerging technologies might support the ?greening? of school and university provision. In contrast to such business-as-usual complacency, this article anticipates ongoing environmental degradation of the planet as radically upending the continued expansion of digital technologies in education. On the one hand, depletion of natural resources and energy curtailments might put paid to established ?abundant? forms of digital technology use. On the other hand, more frequent climate-related disasters might necessitate emergency forms of education for displaced and unsettled populations. As such, the article argues for a new paradigm of educational technology that is both wholly sustainable and targeted towards displaced and disadvantaged populations. The article considers a number of ways that such an ?Ed-Tech Within Limits? might be pursued ? outlining fundamental shifts in thinking necessary to reorient educational technology along environmentally concerned lines.
Publisher: SAGE Publications KerkoCite.ItemAlsoKnownAs: 10.1177/20427530211022951 2339240:IAI4JMQG 2405685:8GL436EN

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4966322 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4966322 10.53832/edtechhub.0115 10.53832/edtechhub.0116 2405685:8HKCSIRC
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

EdTech and Emergency Remote Learning: A Systematic Review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Sam; Nicolai, Susan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651932 previousDOI: 10.5281/zenodo.4917221 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4917221 10.5281/zenodo.5651932 2405685:V6UCUGBZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
ZenodoArchiveID: 4613150 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4613150 2339240:7RV99GRF 2339240:KNG7CIPW 2405685:BHZPG5ZX 2405685:HH8PFJJE 2405685:IG4J94RS 2405685:YMAME8E6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5611467 10.53832/edtechhub.0064 2339240:E542Q29N 2405685:2A5NQEV8 2405685:6JC7RU69 2405685:T3ZQ74QF
Keywords: _r:AddedByZotZen